Impact of condition based maintenance policies on the service level of multi-stage manufacturing systems. (July 2018) - Angius, Alessio; Colledani, Marcello; Yemane, Anteneh
Abstract: Preventive maintenance is crucial for keeping the operational condition of machines but it affects the available productive time of the system. This influences the lot completion time and the delivery dates. Therefore the choice of preventive maintenance policies needs to be taken by jointly considering the actual condition of machines and the service level of the system. In this context, the main contribution of this paper consists in showing how the completion time of a lot is significantly affected by the preventive maintenance policy. This is done by means of numerical illustrations obtained by using both ad-hoc models and a real industrial case. The second contribution relies in the presented methodology that allows the modeling of general synchronous production lines and, given a lot size, the computation of their corresponding service level. The methodology is described in such a way that its extension to different scenarios (such as different system layout and asynchronous machines) is fairly straightforward.